Levinasian thoughts on witnessing: Forgiveness, guilt, and reconciliation. Issue 3 (2nd September 2016) - Ben-Pazi, Hanoch
Abstract : The Truth and Reconciliation Commissions that operated in South Africa in the mid-1990s represented an exceptional political effort to overcome the country's intricate blood-stained history using a mechanism based on foundations of forgiveness in a Christian sense, public trial in a symbolic sense, and commissions of inquiry in a political and legal sense. These commissions constituted one of the most daring and impressive attempts in the history of world politics to transform the national social agenda and to facilitate a shared life for the different groups in South Africa. This article engages in a philosophical discussion of a few major aspects of these commissions via the prism of Levinasian philosophical thought and the philosophical and ethical meaning it assigns to the act of bearing witness.